Prospek Zakat dalam Perekonomian Modern - Kahar Muzakir (Journal of Legal and Cultural Analytics, 2022)
Zakat is a definite obligation, it has been determined as "an obligation from Allah". The hadith emphasizes that people who are assigned to collect and allocate zakat must be prepared and emphasize that zakat must be collected, not left to the wishes of the people who pay zakat. Management of zakat which is organized and carried out systematically based on modern management as referred to in Law No. 38/1999 on zakat management, which was later amended by Law No. 23/2011 regarding zakat management, is intended so that zakat is able to make a real contribution to the improvement of zakat. welfare of Muslims. Today's Modern Economy, especially facing the free market era of the 2015 Asean Economic Community, of course, the contribution of zakat is very much needed to strengthen human resources and support the purchasing power of the Community Economy.